Letramento literário para surdos: aplicação em um escola bilingue - Sales, Taísa Aparecida Carvalho (2024)
Access for deaf people to literary texts is the guiding thread of this thesis. I presented the concept, some genres and examples of works and authors of Deaf Literature and, for this, I have as theoretical foundation Antonio Candido (2002, 2011), Marta Morgado (2011), Rachel Sutton-Spence (2021), Claudio H. Nunes Mourão (2011), Lodenir Karnopp (2008, 2010, 2011, 2022), among others. I presented the concept of literary literacy in the light of Magda Soares (2004) and Rildo Cosson (2014, 2009, 2020, 2021, 2022) and the approaches to deaf studies anchored to deaf pedagogy (Campello (2008), Perlin (2002), Amaral (2020), Strobel (2008), Ladd (2011) through exemplary sequences proposed by Rildo Cosson (2020) and answered the central question: Does literary literacy, following the exemplary sequence proposed by Cosson (2020), work for students To acquire this answer, other questions were necessary for the development of the research, such as: does the bilingual school for the deaf provide access to literary texts for deaf students? What literary genres are presented to students? when approaching literary texts? To this end, I made observations of some Brazilian Sign Language classes, in the 9th year of elementary school 2, at the Escola Bilingue de Surdos – ACAS in the city of Cascavel-PR and applied a Questionnaire to the teacher. Libras and Questionnaire for students about what they understood about Deaf Literature. Given the answers obtained, throughout the class observation process and with the theoretical basis of this research, I developed a textbook with a selection of 6 deaf literary texts, I created 6 exemplary sequences using the model proposed by Cosson (2020), based on the deaf pedagogy, aiming at the literary literacy of deaf students. A workshop was held for Libras teachers at the school and also in the municipality's public network, with the aim of helping teachers develop these students' literary literacy, with a view to greater inclusion in the school context and their approximation of the right to Literature . Of the 6 sequences produced, 2 were applied in the bilingual school. From the results obtained, a negative point emerged: some of the teacher's difficulties in working with deaf literature; and a positive point: more active and enthusiastic participation by students. I realized that it is essential to increase the workload of the deaf literature subject in Libras teacher training courses, according to a comparison of the curricular contents of federal universities. Furthermore, there is a need for training courses for teachers trained in Libras to teach deaf literature so that this professional can train a reader, in this case a deaf student, whose competence goes beyond decoding letters, words, texts , becoming a reader who independently appropriates and perceives the subliminal, the subliminal, the imaginary, that is, a literary reader. The exemplary sequences, even in their small application, proved to be effective, since the teacher, despite not knowing the works so deeply, managed to teach the class and the students understood and developed the proposed activities with a good result. Through reports from the management, after field research, I was informed that there were changes in all aspects, teachers more motivated to use Deaf Literature and students asking for its use.